Understanding underachievers - Larson, Debra Levey; Meridian education Corporation (New Jersey : Meridian Education Corporation, 2000)
Explores some of the many complicated factors which may contribute to a bright child demonstrating a lack of interest in school and learning
Executive producer, Twila Sears
Narrator: Dan Simeone
DVD Format
Keywords: Underachievers -- Education; Motivation in education; Academic achievement